2008
DOI: 10.1021/ja710659y
|View full text |Cite
|
Sign up to set email alerts
|

DFT Studies on the Mechanism of the Diboration of Aldehydes Catalyzed by Copper(I) Boryl Complexes

Abstract: The detailed mechanism for the diboration of aldehydes catalyzed by (NHC)Cu(boryl) complexes (NHC = N-heterocyclic carbene) was studied with the aid of DFT by calculating the relevant intermediates and transition states. The results show that the catalyzed diboration occurs through aldehyde insertion into Cu-B to give a Cu-O-C(boryl) species followed by sigma-bond metathesis with a diboron reagent. It is the "electron-richness", that is, the nucleophilicity of the Cu-boryl bond, which gives rise to a small ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
118
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(133 citation statements)
references
References 101 publications
12
118
0
3
Order By: Relevance
“…The protocol for the previously reported diboration of aldehydes 17 and ketones 18 did not involve the addition of methanol. In the absence of methanol, intermediate 3c (Scheme 2) undergoes transmetalation with a molecule of bis(pinacolato)diboron in the rate determining step to generate the desired dibora compound 3d and regenerate the active catalyst 3a .…”
Section: Resultsmentioning
confidence: 99%
“…The protocol for the previously reported diboration of aldehydes 17 and ketones 18 did not involve the addition of methanol. In the absence of methanol, intermediate 3c (Scheme 2) undergoes transmetalation with a molecule of bis(pinacolato)diboron in the rate determining step to generate the desired dibora compound 3d and regenerate the active catalyst 3a .…”
Section: Resultsmentioning
confidence: 99%
“…Diborane compounds,R 2 B À BR 2 ,a re highly useful synthetic modules for concise synthesis of organoboronates, [1] which are versatile building blocks for the generation of new chemical bonds using the Suzuki-Miyaura crossing-coupling reactions. [3,4] On the other hand, transitionmetal-free catalytic systems for activating the BÀB bond of diborane compounds have also attracted much attention. [3,4] On the other hand, transitionmetal-free catalytic systems for activating the BÀB bond of diborane compounds have also attracted much attention.…”
mentioning
confidence: 99%
“…SR in the presence of pinacolborane (HBpin) undergoes a color change from red to dark red or even brown, which suggests the possible formation of a new species, [(Ph 3 P)CuH]·HBpin, perhaps analogous to that proposed for ligated CuH in the presence of silanes. [16] Control experiments confirmed that net HB does not take place in the absence of CuH. Likewise, a mixture of alkynoate and pinacolborane did not give rise to HB to any noticeable extent, even after prolonged reaction times (several hours).…”
mentioning
confidence: 74%